Canagliflozin Compared With Sitagliptin for Patients With Type 2 Diabetes Who Do Not Have Adequate Glycemic Control With Metformin Plus Sulfonylurea: A 52-week randomized trial - SCHERNTHANER, Guntram; GROSS, Jorge L; ROSENSTOCK, Julio; GUARISCO, Michael; MIN FU; YEE, Jacqueline; KAWAGUCHI, Masato; CANOVATCHEL, William; MEININGER, Gary (Diabetes care, 2013)
To evaluate the efficacy and safety of canagliflozin, a sodium glucose cotransporter 2 inhibitor, compared with sitagliptin in subjects with type 2 diabetes inadequately controlled with metformin plus sulfonylurea. In this 52-week, randomized, double-blind, active-controlled, phase 3 study, subjects using stable metformin plus sulfonylurea (N = 755) received canagliflozin 300 mg or sitagliptin 100 mg daily. Primary end point was change from baseline in A1C at 52 weeks. Secondary end points included change in fasting plasma glucose (FPG) and systolic blood pressure (BP), and percent change in body weight, triglycerides, and HDL cholesterol. Safety was assessed based on adverse event (AE) reports. At 52 weeks, canagliflozin 300 mg demonstrated noninferiority and, in a subsequent assessment, showed superiority to sitagliptin 100 mg in reducing A1C (-1.03% [-11.3 mmol/mol] and -0.66% [-7.2 mmol/mol], respectively; least squares mean difference between groups, -0.37% [95% CI, -0.50 to -0.25] or -4.0 mmol/mol [-5.5 to -2.7]). Greater reductions in FPG, body weight, and systolic BP were observed with canagliflozin versus sitagliptin (P < 0.001). Overall AE rates were similar with canagliflozin (76.7%) and sitagliptin (77.5%); incidence of serious AEs and AE-related discontinuations was low for both groups. Higher incidences of genital mycotic infections and osmotic diuresis-related AEs were observed with canagliflozin, which led to one discontinuation. Hypoglycemia rates were similar in both groups. Findings suggest that canagliflozin may be a new therapeutic tool providing better improvement in glycemic control and body weight reduction than sitagliptin, but with increased genital infections in subjects with type 2 diabetes using metformin plus sulfonylurea.